Life is short, art and scholarship are long: a tribute in memory of Professor Willie Oscar Anku. - Dor, George Worlasi Kwasi (International Library of African Music, 2010)
This tribute, which memorializes Professor Willie Anku, is in two parts. While Part II offers insights from his scholarship on African rhythm, Part I is modeled on a typical Ghanaian eulogy, because I think it appropriate to honor an Africanist with a tribute that draws on elements of his own African culture.
Keywords: African Music